DOM evolution and microbial function during anaerobic digestion under supplementing Fenton sludge: A comparative study - Minhui Cai; Ruize Xia; Zheng Wang; Jun Li; Qing Zhou; Yan Li; Wentao Li; Aimin Li (Journal of Environmental Chemical Engineering, 2026)

Unraveling the Spatiotemporal Dynamics of Alkaloid Biosynthesis During Red Chicory Heading Through Integrated Multi-omics - Baofeng Wang; Ruize Qiu; Qiuzhu Wang; Kexin Li; Lixin Zhu; Xinyang Zhao; Mingliang Jiang; Hong Lang (Plant Molecular Biology Reporter, 2026)

CHBP-loaded mesoporous polydopamine nanoparticles attenuate neuroinflammation and reprogram microglia-neuron crosstalk for spinal cord injury repair - Linyi Xiang; Jiacheng Zhang; Yuzhe Wu; Jingwei Shi; Yun Shu; Ruize Miu; Jiayi Zhao; Junsheng Zhu; Zhichao Tao; Yibo Geng; Haojie Zhang; Zhenglin Li; et al. (Chemical Engineering Journal, 2026)

Loss analysis and performance optimization of high-efficiency G-M type pulse tube cryocoolers operating at liquid helium temperatures - Ruize Li; Haoren Wang; Zhicai Zhang; Kaihao Zhang; Qinyu Zhao; Qingnan Zhang; Ming Wu; Bo Wang; Tao Jin; Zhihua Gan (International Journal of Refrigeration, 2026)

BN-enhanced supramolecular polymer dielectrics with ultrahigh energy density at 200 °C - Tao Lu; Jinfeng Li; Ruize Wang; Shiqi Wang; Tian Zhang (Chemical Engineering Journal, 2026)

Dual-site synergistic tandem effect on Pt single-atoms and CeOx nanoclusters for boosted electrocatalytic detection performance of Cr(VI) - Bo Liang; Lina Li; Yonghuan Zhao; Ruize Xia; Yue Wang; Pangda Dai; Meng Yang; Jingyi Lin; Peihua Li; Xingjiu Huang (Journal of Hazardous Materials, 2026)

Multilayer assembled MFGM mimetics improve digestive fate of human milk structural lipids - Yehui Liang; Ruize Pan; Nian Liu; Xinggang Ni; Yan Yang; ZeYuan Deng; Jing Li (Food Research International, 2026)

Energy dissipation-based emergency temporary reinforcement method for ancient timber structures: experimental and numerical investigations - Ruize Zhang; Xianjie Meng; Yang Cui; Chengya Zhang; Tieying Li; Xiwang Shi (Bulletin of Earthquake Engineering, 2026)

Study of phenoxyethanol-citric acid biphasic pretreatment of sugarcane bagasse for enhanced enzymatic hydrolysis - Jili Liao; Ruize Wang; Xin Li; Ruolin Li; Danna Xie; Xiaoxue Zhao; Jing Wang; Caoxing Huang (Biomass and Bioenergy, 2026)

Raindrop size distribution of monsoon and tropical cyclone events over South China - Ruize Lai; Sheng Hu; Xiantong Liu; Hui Xiao; Huiqi Li (Atmospheric Research, 2026)

From energy drain to resource gain: A high-rate system for synergistic carbon capture and ammonia retention - Ruize Gu; Dongyi Li; Yujie Zhu; Yanling Yu; Wenyong Qin; Weiyan Li; Xinlei Chu; Weihua He; Yujie Feng (Chemical Engineering Journal, 2025)

Charcoal-derived hard carbon anodes with enhanced sodium storage performance for sodium-ion batteries - Shengchen Yang; Yan Li; Chun Chen; Hui Wang; Kaihang Wang; Qingqing Li; Ruize Dong; Manman Chen; Cai Zhao; Weiwei Xu; Lin Sun; Tao Zhang; et al. (Chemical Engineering Journal, 2025)

Contact time and dissolved oxygen concentration modulate carbon capture via shifting microbial metabolism preference in high-rate contact stabilization process - Dongyi Li; Ruize Gu; Tongtong Liu; Fangyue Peng; Dandan Liang; Weihua He; Yujie Feng (Bioresource Technology, 2025)

Quantifying the ENSO’s multifaceted influence on atmospheric predictability across variables and vertical levels - Houbin Song; Jianping Li; Ruize Li; Zhaolu Hou; Shixin Zhen; Hao Li (Climate Dynamics, 2025)

Trade-offs between bio-flocculation and oxidation: Carbon capture pathway governed by SRT in high-rate contact stabilization process - Dongyi Li; Ruize Gu; Fangyue Peng; Zhengyu Yan; Yanfang Song; Tongtong Liu; Dandan Liang; Weihua He; Yujie Feng (Chemical Engineering Journal, 2025)

Acclimatization of salt-tolerant bacteria in a pilot-scale biological treatment system for actual high-salinity wastewater from a chemical industrial park - Yifan Feng; Chunlei Yang; Jun Li; Xinchun Ding; Ruize Xia; Min Hu; Yechao Tian; Yang Pan; Quanxing Zhang; Aimin Li (Journal of Environmental Chemical Engineering, 2025)

A high-capacity separated pulse tube cryocooler working at liquid helium temperatures - Ruize Li; Bo Wang; Qinyu Zhao; Haoren Wang; Zhihua Gan (Science Bulletin, 2025)

Multi-objective optimization of cooling capacity and input power of precooled JT cryocooler working at liquid helium temperature - Changxu Qiu; Yunwei Shen; Ruize Li; Tongfei Wu; Bo Wang; Qinyu Zhao; Zhihua Gan (International Journal of Refrigeration, 2025)

The influence of temperature induced changes in the composition of MFGM on membrane phase transition and nanomechanical properties - Ruize Pan; Yingchao Huang; Teng Wei; Liufeng Zheng; Zhenying Hu; Jingjing Duan; Xian Hao; Zeyuan Deng; Jing Li (Food Research International, 2025)

An assessment of the levels of emerging and traditional organophosphate ester flame retardants in dairy products in China and their combined dietary risks - Ruize Zhou; Jianqiang Geng; Jie Jiang; Bing Shao; Li Lin; Baolong Wang; Yantao Wu; Wei Li (Food and Chemical Toxicology, 2025)

Estimating the decadal-scale climate predictability limit using nonlinear local Lyapunov exponent with optimal local dynamic analogues - Ruize Li; Jianping Li; Zhaolu Hou; Ruipeng Sun; Shixin Zhen; Houbin Song (Climate Dynamics, 2025)

Research on effective mercury removal from flue gas over Cl/Br/I/O modified adsorbents at ultra-low temperature - Lingxuan Chen; Ruize Sun; Guangqian Luo; Tong Sun; Li Wang; Leicong Liang; Yulu Zhang; Ping Xiao; Shiqing Wang; Xian Li; Hong Yao (Journal of Environmental Chemical Engineering, 2024)

Enhancing phosphorus release and recovery from waste activated sludge by citric acid treatment and cyclic extraction - Fangyue Peng; Weihua He; Ruize Gu; Dandan Liang; Dongyi Li; Yujie Feng (Chemical Engineering Journal, 2024)

Correction: Biological characterization of emerging fungal pathogen Colletotrichum associated with mango (Mangifera indica L.) post-harvest anthracnose from Vietnam - Ruize Tao; Bingjuan Yang; Li Lin; Shahzad Munir; Yuchuan Li; Xi Wang; Min Huang (Molecular Biology Reports, 2024)

Biological characterization of emerging fungal pathogen Colletotrichum associated with mango (Mangifera indica L.) post-harvest anthracnose from Vietnam - Ruize Tao; Bingjuan Yang; Li Lin; Shahzad Munir; Yuchuan Li; Xi Wang; Min Huang (Molecular Biology Reports, 2024)

CDK5 Upregulated by ELF3 Transcription Promotes IL-1β-induced Inflammation and Extracellular Matrix Degradation in Human Chondrocytes - Xuyuan Zhang; Ruize Zhang; Yinhai Wang; Liang Li; Zong Zhong (Cell Biochemistry and Biophysics, 2024)

Decoupling the influence of NOx in flue gas on the application of nano-amorphous selenium for mercury removal - Li Wang; Yu Li; Ruize Sun; Renjie Zou; Yongda Huang; Mingyu Yu; Jing Liu; Guangqian Luo; Hong Yao (Science of The Total Environment, 2024)

Influence of low-temperature pyrolysis pretreatment on the co-combustion performance of coal and waste polyvinyl chloride/tire - Mengli Zhou; Yang Xu; Guangqian Luo; Ruize Sun; Renjie Zou; Chunhui Sun; Xian Li; Hong Yao (Fuel, 2024)

Research on mercury re-release model in wet flue gas desulfurization (WFGD) in coal-fired power plants - Ruize Sun; Mingyu Yu; Guangqian Luo; Li Wang; Mengli Zhou; Xinpei Lu; Xian Li; Hong Yao (Chemical Engineering Journal, 2024)

Effect of the main properties of membrane materials on denitrification of hydrogen-based membrane biofilm reactors (H2-MBfRs) - Yinghui Zhang; Kun Dong; Meng Zhang; Xiaofei Wang; Xuehong Zhang; Dunqiu Wang; Ruize Sun; Haixiang Li; Wenjie Zhang (Journal of Water Process Engineering, 2024)

Experimental and numerical study on NOx reduction from NH3/DME/air flame using fuel staging method - Mingyu Yu; Guangqian Luo; Ruize Sun; Li Wang; Xian Li; Hong Yao (Fuel, 2024)

Contamination of dairy products with tris(2,4-di-tert-butylphenyl) phosphite and implications for human exposure - Ruize Zhou; Jianqiang Geng; Jie Jiang; Bing Shao; Li Lin; Tongna Mu; Baolong Wang; Ting Liu (Food Chemistry, 2024)

Ammonia partial cracking over low-cost Ni catalysts for enhancing combustion - Mingyu Yu; Ruize Sun; Guangqian Luo; Li Wang; Xian Li; Hong Yao (Fuel, 2024)

Emerging organophosphite and organophosphate esters in takeaway food and the implications for human exposure - Ruize Zhou; Jianqiang Geng; Jie Jiang; Bing Shao; Baolong Wang; Yu Wang; Minggang Li (Environmental Science and Pollution Research, 2024)

Influence of the preceding August-September-October tropical cyclones over the Western North Pacific on the following spring sea ice in the Beaufort Sea: the bridging role of El Niño - Dingjia Ye; Jianping Li; Fei Huang; Ruipeng Sun; Xinxin Tang; Ruize Li (Climate Dynamics, 2024)

Distinct phosphorylation optimizes pathogen-induced PA and ROS bursts - Kaihuai Li; Ruize Zhang; Yong Wang; Fengquan Liu; Zheng Qing Fu (Molecular Plant, 2024)

Experimental and theoretical study on recovered nano amorphous selenium as efficient adsorbents for mercury capture from flue gas - Li Wang; Yu Li; Ruize Sun; Renjie Zou; Yongda Huang; Guangqian Luo; Hong Yao (Journal of Cleaner Production, 2024)

Insight into the influence of environmental factors on selenite removal from desulfurization wastewater by NZVI@AC: An experimental and theoretical study - Li Wang; Yu Li; Renjie Zou; Ruize Sun; Hong Tian; Guangqian Luo; Hong Yao (Journal of Water Process Engineering, 2024)

Launching, perceiving, and diminishing of airborne signals - Mikayla Carty; Ruize Zhang; Ziyue Li; Daowen Wang; Zheng Qing Fu (Molecular Plant, 2023)

Plasma-assisted synthesis of nano-sulfur adsorbent for efficient removal of mercury from flue gas - Ruize Sun; Guangqian Luo; Mingyu Yu; Li Wang; Xinpei Lu; Xian Li; Hong Yao (Chemical Engineering Journal, 2023)

Adsorption of Li+ by imprinted capacitor deionization — A new method for selective recovery of valuable lithium in acidic solutions - Ning Han; Yifei Li; Haisen Peng; Ruize Gao; Qiongqiong He; Zhenyong Miao; Keji Wan (Desalination, 2023)

Fluorescent probe/hydrogel-based portable platform for ultrasensitive on-site detection of explosive particles containing nitrite - Jiawei Zhang; Tianyu Hu; Baojiao Xiong; Xufan Zheng; Ruize Wang; Panpan Zhu; Jin Chen; Tingting Cong; Yuda Li; Xunchang Wang (Chemical Engineering Journal, 2023)

Occurrence and migration of organophosphite and organophosphate esters into food simulants from single-use food packaging in China - Ruize Zhou; Jianqiang Geng; Jie Jiang; Li Lin; Jing Zhang; Yunjia Yang; Xiaojun Wang; Yumin Niu; Bing Shao (Environmental Pollution, 2023)

Theoretical and experimental study for the transient behavior of a linear compressor during pulse tube cryocooler cool down process - Bo Wang; Ruize Li; Yijun Chao; Changpei Zhuang; Qinyu Zhao; Shuze Sun; Chunjie Yan; Zhihua Gan (International Journal of Refrigeration, 2023)

Extreme rainfall in Northern China in September 2021 tied to air–sea multi-factors - Yue Sun; Jianping Li; Hao Wang; Ruize Li; Xinxin Tang (Climate Dynamics, 2023)
The September rainfall over Northern China (NC) in 2021 was the heaviest since 1961 and had unprecedented socioeconomic impacts. Holding the hypothesis that the drivers of extreme climate events usually contain extreme factors, we firstly propose the Ranking Attribution Method (RAM) to find the possible air–sea multi-factors responsible for this rainfall event. Via the atmospheric bridges of zonal-vertical circulation and Rossby wave energy propagation, the remote factors of warm sea surface temperature anomalies (SSTA) over the tropical Atlantic, cold SSTA over the tropical Pacific, Southern Annular Mode-like pattern in the Southern Hemisphere and North Pacific Oscillation-like pattern in the Northern Hemisphere jointly strengthened the Maritime Continent (MC) convection and Indian monsoon (IM). Through meridional-vertical circulation, the intensified MC convection enhanced the subtropical high over southern China and induced ascending motion over NC . The local factor of extreme air acceleration in the east Asian upper-level jet entrance region further anchored the location of the southwest-northeast rain belt. The strengthened IM and subtropical high over southern China induced considerable moisture transport to the rain belt via two moisture channels. The combined effect of these extreme dynamic and moisture conditions formed this unprecedented rainfall event. This study suggests that the RAM can effectively reveal the factors that contributed to this extreme rainfall event, which could provide a new pathway for a better understanding of extreme climate events.

Effects of desert riparian vegetation roots on the riverbank retreat process in the Tarim River in China - Quanli Zong; Tiegang Zheng; Ruize Tang; Kai Jin; Lin Li; Peng Qin; Chunxia Liu (Journal of Hydrology, 2023)

Expanding Asgard members in the domain of Archaea sheds new light on the origin of eukaryotes - Ruize Xie; Yinzhao Wang; Danyue Huang; Jialin Hou; Liuyang Li; Haining Hu; Xiaoxiao Zhao; Fengping Wang (Science China Life Sciences, 2022)

Different physiological responses of C3 and C4 plants to nanomaterials - Tonghao Bai; Peng Zhang; Zhiling Guo; Andrew J. Chetwynd; Mei Zhang; Muhammad Adeel; Mingshu Li; Kerui Guo; Ruize Gao; Jianwei Li; Yi Hao; Yukui Rui (Environmental Science and Pollution Research, 2021)

Task-related functional magnetic resonance imaging-based neuronavigation for the treatment of depression by individualized repetitive transcranial magnetic stimulation of the visual cortex - Zhijun Zhang; Hongxing Zhang; Chun-Ming Xie; Meng Zhang; Yachen Shi; Ruize Song; Xiang Lu; Haisan Zhang; Kun Li; Bi Wang; Yongfeng Yang; Xianrui Li; et al. (Science China Life Sciences, 2021)

Endothelial retinoblastoma protein reduces abdominal aortic aneurysm development via promoting DHFR/NO pathway-mediated vasoprotection - Yu Cao; Da Xiong; Ruize Kong; Guolin Dai; Minghua Zhong; Li Li; Jinping Zhang; Lihong Jiang; Hongrong Li (Molecular and Cellular Biochemistry, 2019)

A miR-18a binding-site polymorphism in CDC42 3′UTR affects CDC42 mRNA expression in placentas and is associated with litter size in pigs - Ruize Liu; Dadong Deng; Xiangdong Liu; Yujing Xiao; Ji Huang; Feiyu Wang; Xinyun Li; Mei Yu (Mammalian Genome, 2019)

Performance evaluation of TMPA version 7 estimates for precipitation and its extremes in Circum-Bohai-Sea region, China - Dejuan Jiang; Hua Zhang; Ruize Li (Theoretical and Applied Climatology, 2017)